Narrating the past: archaeological epistemology, explanation and communication : proceedings of the 6th Annual Conference of the Central European Theoretical Archaeology Group, held at the University of Leizig (Germany) on 12-13 September 2019 - Miera, Jan (Archaeolingua, 2023)
Humans are wired for storytelling. We continually construct our identities and defi ne our sense of belonging through narratives. They help us make sense of the past and serve as a frame of reference for understanding the present. On 12 and 13 September 2019, students and post-docs from the UK, Poland, Czech Republic, and Germany met at the University of Leipzig to discuss how archaeology contributes to these processes and, thereby, the overall understanding of what it means to be human. The participants addressed this topic from a variety of perspectives by highlighting, for example, the role of archaeological epistemology, examining the systematics of explanations in prehistoric archaeology, and exchanging experiences regarding the communication between the scientific community and the public. Unanimously, the contributions illustrate the importance of a refl ective and transparent engagement with the processes of knowledge production and narration in archaeology.
Keywords: Konferenzschrift -- 2019 -- Leipzig; Archäologie; Vor- und Frühgeschichte; Europa